2000
DOI: 10.1016/s0378-1097(00)00029-x
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular hyaluronidase gene (hylA) of Streptococcus pyogenes

Abstract: Group A streptococci produce an extracellular hyaluronidase (hyaluronate lyase) which may be associated with the spread of the organism during infection. The gene for this hyaluronidase (hylA) encodes an 868 amino acid protein with a molecular size of 99 636 Da. Cleavage of the proposed signal peptide results in an extracellular protein of 95 941 Da. Comparison with other bacterial hyaluronidases indicates strong similarities to the genes from Streptococcus pneumoniae, Streptococcus agalactiae and Staphylococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
(23 reference statements)
0
17
1
1
Order By: Relevance
“…We found that frequency of hyaluronidase expression among unrelated clinical strains collected from the University of Michigan Hospitals was significantly lower than published results (8). We also observed that the most clinically significantly M types (M1 and M3) do not produce an active enzyme in vitro.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…We found that frequency of hyaluronidase expression among unrelated clinical strains collected from the University of Michigan Hospitals was significantly lower than published results (8). We also observed that the most clinically significantly M types (M1 and M3) do not produce an active enzyme in vitro.…”
Section: Discussioncontrasting
confidence: 58%
“…that are not homologous to hylA at the level of DNA sequence or protein product. Extracellular hyaluronidase activity is attributable to the product of the hylA gene, HylA, whereas HylP and its analogues are believed to be phage associated, facilitating penetration of the capsule by streptococ-cal phages (8,10). Although all GAS have a hylA gene, only a small percentage of clinical strains (Ͻ25%) produce a detectable amount of HylA when grown in vitro (10).…”
mentioning
confidence: 99%
“…S. agalactiae hylB encodes hyaluronate lyase (hyaluronidase), a putative virulence factor that is involved in cleaving hyaluronic acid, a component of the extracellular matrix in many tissues (30). Hyaluronidases have also been found to be important virulence factors in other gram-positive organisms, such as Streptococcus pyogenes (22). Overall, human isolates showed a significantly lower average hyaluronidase activity than bovine isolates, indicating that S. agalactiae isolates from cattle and human invasive cases also represent phenotypically distinct populations.…”
Section: Discussionmentioning
confidence: 99%
“…A fragment of this serine protease was recently described to be present in culture supernatant of S. pyogenes (28). Recently, an LPXTGX-containing hyaluronidase (HylA) in S. pyogenes was described (24). In S. pneumoniae, a similar hyaluronidase containing a typical cell wall sorting signal has been proposed to be cell wall attached (5,25).…”
Section: Construction Of a Tripartite Pattern By Analysis Of Coohtermmentioning
confidence: 99%